Kebijakan Yuridis Deportasi Terhadap Warga Negara Asing (Studi Kasus Deportasi Terhadap Warga Negara Asing Di Bali) - Ni Putu Christina Elzaputri Rahayu; I Made Minggu Widyantara; Ni Made Sukaryati Karma (Fakultas Hukum Universitas Warmadewa, 2025)
Deportation is a term for an immigration administrative action against foreign nationals who enter Indonesian territory and are suspected of violating Indonesian laws and regulations or committing dangerous acts that can threaten public safety and order. The formulation of the problem raised is, How is the juridical regulation of deportation of foreign nationals in Indonesia regulated in the applicable laws and regulations, How is the juridical policy of deportation of foreign nationals? The writing method used is normative legal research method. From the results obtained, the juridical regulation of deportation of foreigners in Indonesia is regulated in Law Number 6 of 2011 concerning Immigration. Based on Article 75 paragraph (1) of the Immigration Law. The policy carried out, if proven to have committed an immigration violation, the foreign national will be given a deportation order. The deportation order is signed by the Head of Immigration Office Class I Special TPI Denpasar. Foreigners who are deported will be put on the catch list.